(untitled) (Revista Latino-Americana de Enfermagem, 2002)
The purpose of this study was to show the prevalence of characteristics in former students from the Specialization Course on Obstetric Nursing of the University of São Paulo College of Nursing, Brazil. The population consisted of 92 former students who graduated in 1980 to 1985, of whom 50% worked in the field of obstetric nursing. Of these, 73,2% were clinical nurses and 26,8% were university faculty. Concerninng those who no longer performed in that field, 76,0% did so after graduation and 24,0% never worked in the area. Regarding professional satisfaction, 71,7% reported to be satisfied and 28,3% were dissatisfied. The reasons given for stopping working in that area suggest very important points to be analyzed professional representation entities as well as by those who are responsible for the education of these professionals.